Communication expectations of critically ill patients and their families - Ervin, Jennifer N. (Journal of Emergency and Critical Care Medicine, 2019)
Little is known about specific expectations family members and other types of surrogates have regarding clinician interaction. The objective of this study is to describe communication expectations regarding clinician engagement when surrogates represent patients who are too critically ill to advocate on their own behalf. As part of a larger study, a panel of 44 former patients and surrogate decision makers of a 20-bed medical intensive care unit (ICU) housed within a large academic hospital in the Midwestern United States responded to an online survey. Findings suggest that participants held different expectations for different intensive care providers in that 98% expected to talk to an attending physician within 48 hours of their loved one being admitted to the ICU, while 88% expected to have spoken with a registered nurse, and 74% with a respiratory therapist. Only half expected to have talked with a resident or fellow, and a third to a social worker. Regarding communication frequency, 95% of participants expected to interact with the care team at least once a day, and 74% preferred for contact to be initiated by clinicians. Together this suggests that expectations for surrogate-clinician communication more closely aligned with current guidelines for family-centered care than they are with actual practice.